Intracellular accumulation dynamics and fate of zinc ions in alveolar epithelial cells exposed to airborne ZnO nanoparticles at the air–liquid interface. Issue 1 (February 2015) - Mihai, Cosmin; Chrisler, William B.; Xie, Yumei; Hu, Dehong; Szymanski, Craig J.; Tolic, Ana; Klein, Jessica A.; Smith, Jordan N.; Tarasevich, Barbara J.; Orr, Galya
Abstract Airborne nanoparticles (NPs) that enter the respiratory tract are likely to reach the alveolar region. Accumulating observations support a role for zinc oxide (ZnO) NP dissolution in toxicity, but the majority of in-vitro studies were conducted in cells exposed to NPs in growth media, where large doses of dissolved ions are shed into the exposure solution. To determine the precise intracellular accumulation dynamics and fate of zinc ions (Zn2+) shed by airborne NPs in the cellular environment, we exposed alveolar epithelial cells to aerosolized NPs at the air–liquid interface (ALI). Using a fluorescent indicator for Zn2+, together with organelle-specific fluorescent proteins, we quantified Zn2+ in single cells and organelles over time. We found that at the ALI, intracellular Zn2+ values peaked 3 h post exposure and decayed to normal values by 12 h, while in submerged cultures, intracellular Zn2+ values continued to increase over time. The lowest toxic NP dose at the ALI generated peak intracellular Zn2+ values that were nearly three-folds lower than the peak values generated by the lowest toxic dose of NPs in submerged cultures, and eight-folds lower than the peak values generated by the lowest toxic dose of ZnSO4 or Zn2+. At the ALI, the majority of intracellular Zn2+ was found in endosomes and lysosomes as early as 1 h post exposure. In contrast, the majority of intracellular Zn2+ following exposures to ZnSO4 was found in other larger vesicles, with less than 10% in endosomes and lysosomes. Together, our observations indicate that low but critical levels of intracellular Zn2+ have to be reached, concentrated specifically in endosomes and lysosomes, for toxicity to occur, and point to the focal dissolution of the NPs in the cellular environment and the accumulation of the ions specifically in endosomes and lysosomes as the processes underlying the potent toxicity of airborne ZnO NPs.